How Students with Autism Spectrum Disorder Perform in Regular and Special Education Classrooms - Yao, Leying (Transactions on Social Science, Education and Humanities Research, 2024)
The educational placement of ASD child learners has been a topic of dispute in both the clinical and academic domains. It was formerly common practice to enroll child learners with ASD in separate special education programs because it was believed that these environments may provide more intensive and customized therapies. There has been a notable surge towards inclusive education in recent decades, influenced by broader cultural trends promoting inclusion and equality for people with disabilities. The current research compares and contrasts the effects of comprehensive and special education environments on the study patterns of students diagnosed with ASD. It evaluates how inclusive classrooms significantly boost the learning behaviors and social skills of child learners with ASD, subject to the practical adaptation of teaching methodologies, a supportive school culture, and educators’ readiness to accommodate these kids’ particular requirements. By comparison, special education settings facilitate the learning and development of child learners with ASD by offering specialized attention, targeted treatments, and a collaborative approach that addresses their specific needs. Special education environments may offer customized teaching methods that address individual learning needs, potentially enhancing academic skills. This research aims to determine the more effective educational approach for meeting the varied learning needs of child learners with ASD, considering the contributing factors in both settings. The optimal educational approach for child learners with ASD involves leveraging the unique advantages of inclusive classrooms and special education settings, guided by a commitment to understanding and meeting their diverse needs to facilitate their holistic development and societal inclusion. The results are intended to inform the ongoing discussion about the best educational practices for child learners with ASD, providing evidence to help educators, policymakers, and parents create the most supportive learning environments for this distinct group.